2021
DOI: 10.3390/cells10040791
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding Partners of Dysregulated miRNAs in Parkinson’s Disease Serum

Abstract: Accumulating evidence suggests that microRNAs (miRNAs) are a contributing factor to neurodegenerative diseases. Although altered miRNA profiles in serum or plasma have been reported for several neurodegenerative diseases, little is known about the interaction between dysregulated miRNAs and their protein binding partners. We found significant alterations of the miRNA abundance pattern in serum and in isolated serum-derived extracellular vesicles of Parkinson’s disease (PD) patients. The differential expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(13 reference statements)
1
5
0
1
Order By: Relevance
“…A number of studies examined microRNAs packaged in exosomes from cerebrospinal fluid and plasma of Parkinson's disease patients, cultured cells, and rat models of Parkinson's disease [233][234][235][236]. Several microRNAs were differentially associated with exosomes from the diseased samples as compared to controls.…”
Section: Role Of Exosomes In Neurodegenerative Diseasesmentioning
confidence: 99%
“…A number of studies examined microRNAs packaged in exosomes from cerebrospinal fluid and plasma of Parkinson's disease patients, cultured cells, and rat models of Parkinson's disease [233][234][235][236]. Several microRNAs were differentially associated with exosomes from the diseased samples as compared to controls.…”
Section: Role Of Exosomes In Neurodegenerative Diseasesmentioning
confidence: 99%
“…According to the literature, hsa-miR-8063 was found to inhibit pancreatic cancer progression through inducing inhibition on ZFP91 [63], to suppress the epithelial–mesenchymal transition of lung cancer cells by regulating its target gene MAGAT3 [64], and to induce cell migration through inhibition of the tumour suppressor FOXN2 [65]. Hsa-mir-4745–5p was strongly dysregulated in Parkinson’s disease (PD) and can be directly regulated by HNF4a [66], which was identified as a longitudinal PD blood biomarker [67]. Hsa-mir-4745–5p was also observed to be upregulated in patients with colorectal cancer [68].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, exosomal miR‐21‐3p, miR‐22‐3p and miR‐223‐5p were significantly different between Controls from PD cases and miR‐425‐5p, miR‐21‐3p, and miR‐199a‐5p distinguished between PD cases and progressive supranuclear palsy which are often misdiagnosed (Manna et al, 2021). However, a recent study found altered miRNA patterns between Control and PD cases, with the highest discriminatory value obtained in serum when compared to serum‐derived EVs (Ruf et al, 2021).…”
Section: Evs and Clinical Research On Neurodegenerative Disordersmentioning
confidence: 99%